Komunitas Peduli Jantung (KOPEJA) Sebagai Upaya Pencegahan Terjadinya Penyakit Jantung Koroner - sangadji, faisal (LPPM STIKES Madani, 2022)
Coronary heart disease (CHD) is the main cause of death and illness in the world and is a health problem in Indonesia. There are still many Indonesians who do not realize the high risk of suffering from this disease. Bantul Regency is one of the areas where the incidence of CHD continues to increase from time to time. Based on the data of the Piyungan Health Center, the symptoms that lead to CHD are often found in the community such as Kradenan. Unhealthy lifestyles were found in the community such as smoking, the wrong diet, and excessive salt consumption. CHD control is exacerbated by the lack of prevention which can increase morbidity and mortality. The purpose of this service is to form a heart care community named KOPEJA as a cadre whose role is to detect and prevent people from CHD by teaching and practicing how to live a healthy lifestyle and avoid risk factors. This service activity involves the health cadres of Nyamplung Kradenan. The method used is to empower health cadres who have been taught how to check and provide health education related to CHD prevention. Furthermore, KOPEJA takes data from the community to detect the presence or absence of CHD risk factors and conducts health education using the prepared media. The result of the activity is the formation of KOPEJA. Most of the residents were smoking (55%), had hypertension (33%), and pre-hypertension (14%), were increasing blood sugar (34%). After being given health education by KOPEJA there was an increase in the level of knowledge of the residents. KOPEJA could check blood pressure, blood sugar, and be able to conclude the results as well as provide health education about the prevention of CHD to residents properly.